2009
DOI: 10.1002/art.24873
|View full text |Cite
|
Sign up to set email alerts
|

Improved influenza and pneumococcal vaccination in rheumatology patients taking immunosuppressants using an electronic health record best practice alert

Abstract: Objective. To examine whether an electronic health record (EHR) best practice alert (BPA), a clinical reminder to help guideline adherence, improved vaccination rates in rheumatology patients receiving immunosuppressants. Guidelines recommend yearly influenza and pneumococcal vaccination with revaccination for patients age >65 years who are taking immunosuppressive medications. Results. PostBPA influenza vaccination rates significantly increased (47% to 65%; P < 0.001), with significant improvement at both sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 40 publications
2
74
3
Order By: Relevance
“…Literature review highlights three main findings supported by our study: vaccine coverage rates against influenza and pneumococcus are always suboptimal (from 34% to 63% and from 11%% to 39%, respectively) [36][37][38][39][40]; pneumococcal vaccination uptakes are lower than influenza vaccine uptakes; and vaccine uptake rates vary according to disease groups [35,[41][42][43].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Literature review highlights three main findings supported by our study: vaccine coverage rates against influenza and pneumococcus are always suboptimal (from 34% to 63% and from 11%% to 39%, respectively) [36][37][38][39][40]; pneumococcal vaccination uptakes are lower than influenza vaccine uptakes; and vaccine uptake rates vary according to disease groups [35,[41][42][43].…”
Section: Discussionsupporting
confidence: 62%
“…The reported rate of vaccination against pneumococcus was 49% (95%CI [47][48][49][50]); 51% (95%CI [49-53]) in the AI group, 36% (95%CI [30][31][32][33][34][35][36][37][38][39][40][41][42][43]) in the Tx group and 39% (95%CI [33][34][35][36][37][38][39][40][41][42][43][44]) in the MBD group (Table 3).…”
Section: Pneumococcal Vaccinementioning
confidence: 99%
“…Improved comanagement between primary care and rheumatologists probably might improve this situation and lead to higher vaccination rates. In the United States, the use of an electronic health record with best practice alert signiWcantly increased inXuenza and pneumococcal vaccination in rheumatologic patients taking immunosuppressive drugs [23]. Therefore, speciWc national surveillance strategies seem to be required.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of a study in the USA reported that using a computerized medical file (French acronym = DMI) would increase the opportunity to update pediatric vaccinations with vaccinations performed earlier [15]. Likewise, a tool was set up in a rheumatology unit, reminding physicians when immuno-depressed patients needed to be vaccinated against the pneumococcus and influenza (electronic clinical reminder) [16]. The physicians had to either prescribe the vaccine or mention reasons for non-vaccination in the computerized alert system.…”
Section: Discussionmentioning
confidence: 99%